Association between gastric polyps and decreased bone mineral density in patients with chronic gastritis - Guotao Liu; Jianyuan Zhang (Scientific Reports)
Abstract Gastric polyps indicate the disturbance of gastric microecology and inflammatory status, which may affect bone metabolism. We aimed to investigate the association between gastric polyps and bone mineral density (BMD) in patients with chronic gastritis (CG). In this cross-sectional study, we collected the clinical data of 627 inpatients with CG between July 2017 and August 2022. Gastric polyps were diagnosed through gastroscopy. BMD was measured using dual energy X-ray absorptiometry. Osteopenia or osteoporosis was defined as decreased BMD. Linear regression analysis was employed to assess the relationship between BMD with gastric polyps. Logistic regression analysis was conducted to evaluate the correlation between decreased BMD and gastric polyps. In results, the prevalence of gastric polyps in males and females with CG was 17.3% and 18.3%, respectively. The occurrence of decreased BMD was observed in 51.4% and 65.1% of males and females, respectively. Gastric polyps were negatively correlated with lumbar spine, femoral neck, and total femur BMD (β=-0.025, -0.043, -0.029, p ≤ 0.005) in females with CG. Furthermore, gastric polyps significantly elevated the risk of osteoporosis or osteopenia (OR = 2.672, p = 0.010) among females with CG. However, no significant correlation between gastric polyps and BMD was detected in males with CG. In addition, gastric polyps in females were positively correlated with hypertension and high low-density lipoprotein cholesterol levels, while negatively correlated with high phosphorus levels. In conclusion, gastric polyps are negatively correlated with BMD and significantly increase the risk of osteoporosis or osteopenia in females with CG.